Ambiente escolar e atividade física em escolares de Pelotas, RS - Marques, Margarete Oleiro (2012)
Introduction and Objectives: In view of the scientific evidence point to the benefits of AF in childhood / adolescence as a factor associated with a healthy lifestyle, and the role of these training school habits, it becomes essential to understand the barriers and facilitators that the school is available for children and adolescents as a means of assist in routing changes needed to be made. This study aimed to describe the school environment in relation to and supply conditions for PA practice, and investigate the level of FY schoolchildren aged eight to 12 years in Pelotas. Methodology: Cross sectional study school-based. Sampling was performed in duplicate in conglomerate stage, stratified network level and teaching series. Twenty schools were Featured: 9 municipal, 6 and 5 private state. In each 50 students were selected, from 2nd to 6th grade, aged eight to 12 years. Children were weighed and measured and were applied at the following instruments: interviews with the children, identification of the physical environment school; questionnaires on facilities and equipment available in AF questionnaire for school and on the provision of extracurricular activities (AEC) and access to school infrastructure. Results: The schools have space physical mandatory for AF, but the infrastructure found in most (75%) is not suited to the climate of the city, not having spaces covered, and is not easily accessible to students. The prevalence of inactivity among schoolchildren was high, with only ¼ of them were classified as active. Although the majority (80%) of schools AEC offers, they reach a limited number of students. According professionals involved, the infrastructure and materials not available are not enough good quality. Conclusion: It is urgent and necessary interventions that are conducted at the school level, especially through the implementation of public policies, with emphasis on improving spaces for the practice of PA towards the adoption of a lifestyle between healthy school through regular practice of AF